Baveno Criteria Safely Identify Patients With Compensated Advanced Chronic Liver Disease Who Can Avoid Variceal Screening Endoscopy: A Diagnostic Test Accuracy Meta-Analysis - Szakács, Zsolt; Erőss, Bálint; Soós, Alexandra; Mátrai, Péter; Szabó, Imre; Pétervári, Erika; Bajor, Judit; Farkas, Nelli; Hegyi, Péter; Illés, Anita; Solymár, Margit; Balaskó, Márta; et al. (Frontiers in Physiology, 2019)
Background: The Baveno VI Consensus Workshop defined new criteria (liver stiffness measured by transient elastography <20 kPa and platelet count >150x109 cells/L) to identify those patients with compensated advanced chronic liver diseases (cACLD) who are unlikely to have high-risk esophageal varices and can safely avoid variceal screening endoscopy. This meta-analysis aimed to quantify the safety and efficacy of these criteria. Methods: A systematic search was conducted in nine databases for diagnostic accuracy studies. Eligible papers discussed chronic liver diseases (CLD) and tested Baveno criteria against endoscopic variceal screening. Our main focus was the predictive power of Baveno criteria for varices needing treatment. We calculated pooled spared endoscopy rate, sensitivity, specificity, and negative and positive predictive values with 95% confidence intervals (CIs). Heterogeneity was tested by I2-statistics and explored by subgroup analysis (cACLD) and meta-regression. Results: The search yielded 27 eligible papers including 6739 CLD cases. Pooled spared endoscopy rate was 26.4% (CI: 21.6-31.5%; I2=95.1%). Pooled negative predictive value proved to be 99.3% (CI: 98.4-99.8%; I2=21.5%). In the subgroup of cACLD, heterogeneity disappeared while negative predictive value was maintained. Pooled sensitivity was 97.9% (CI: 95.1-99.7%; I2=49.4%), with an I2=9.8% in the subgroup of cACLD. Pooled positive predictive value was 18.1%, (CI: 13.3-23.5%; I2=93.0%). Pooled specificity was 31.0% (CI: 23.5-39.0%; I2=96.5%). Meta-regression proved that body mass index (p=0.042), the percentage of non-alcoholic fatty liver disease in the study population (p=0.038), and platelet count (p=0.027) correlated positively with specificity. Conclusions: The application of Baveno criteria significantly reduces the number of unnecessary variceal screening endoscopies while being safe: patients with liver stiffness <20 kPa and platelet count >150x109 cells/L carry a very low risk of having varices needing treatment.